Two lanthanide-based metal–organic frameworks for highly efficient adsorption and removal of fluoride ions from water. Issue 16 (4th April 2017) - Ma, Aiqing; Ke, Fei; Jiang, Jing; Yuan, Qiaoyu; Luo, Zhidong; Liu, Jianqiang; Kumar, Abhinav
Abstract : The contamination of water with fluoride (F − ) is a source of mounting concern for global public health, and the removal of fluoride is quite important and challenging. Abstract : The contamination of water with fluoride (F − ) is a source of mounting concern for global public health, and the removal of fluoride is quite important and challenging. In this study, two new lanthanide-based metal–organic frameworks (MOFs), [Ce(L1)0.5 (NO3 )(H2 O)2 ]·2DMF (1 ) and [Eu3 (L2)2 (OH)(DMF)0.22 (H2 O)5.78 ]·guest (2 ) (H4 L1 = 2, 5-di(3′, 5′-dicarboxylphenyl)benzene and H4 L2 = 3, 5-bis(isophthalic acid)-1 H -1, 2, 4-triazole) are designed, synthesized and characterized. Both MOFs are tested for their adsorption capacity for fluoride ions and different uptake times from contaminated water. The investigation indicates that1 displays a much higher adsorption capacity (103.95 mg g −1 ) and faster uptake rates (1.79 g mg −1 min −1 ) for fluoride ion than that of2 . The presented investigation is the first report in which lanthanide-based MOFs are used for the removal of fluoride ions from water.